Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10803-006-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

The Gluten-Free, Casein-Free Diet In Autism: Results of A Preliminary Double Blind Clinical Trial

Abstract: This study tested the efficacy of a gluten-free and casein-free (GFCF) diet in treating autism using a randomized, double blind repeated measures crossover design. The sample included 15 children aged 2-16 years with autism spectrum disorder. Data on autistic symptoms and urinary peptide levels were collected in the subjects' homes over the 12 weeks that they were on the diet. Group data indicated no statistically significant findings even though several parents reported improvement in their children. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
192
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(209 citation statements)
references
References 21 publications
(11 reference statements)
2
192
0
15
Order By: Relevance
“…Increased gut permeability and elevated level of bacterial metabolic products such as LPS leading to increased proinflammatory cytokines such as IL-6 have also been shown in children with ASD. 144 A few small clinical trials have shown beneficial effects for gluten free and casein free diets on symptoms of children with ASD 145,146 that could potentially be attributed to the change in gut microbiota. 4,8,19,61,128,147 Furthermore, in children with autism, the frequency of GI symptoms is increased 148,149 and has been attributed to a low-grade chronic inflammation in the GI tract caused by altered gut microbiota.…”
Section: Emerging Areasmentioning
confidence: 99%
“…Increased gut permeability and elevated level of bacterial metabolic products such as LPS leading to increased proinflammatory cytokines such as IL-6 have also been shown in children with ASD. 144 A few small clinical trials have shown beneficial effects for gluten free and casein free diets on symptoms of children with ASD 145,146 that could potentially be attributed to the change in gut microbiota. 4,8,19,61,128,147 Furthermore, in children with autism, the frequency of GI symptoms is increased 148,149 and has been attributed to a low-grade chronic inflammation in the GI tract caused by altered gut microbiota.…”
Section: Emerging Areasmentioning
confidence: 99%
“…73 The reviewed trials included a 12-month, single-blind trial (n ϭ 10) of Norwegian children; this study showed some reduction in autistic traits and modest improvement on standardized measures of communication and interaction and social isolation. 72 The second study reviewed was a small, 12-week, randomized, double-blind study (n ϭ 15) that revealed no statistically significant benefits of the diet, although several parents had reported improvement in their children 74 ; the authors stressed an urgent need for well-conducted and adequately powered, randomized, controlled trials in this area.…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…For example, while gluten-and 74 casein-free diets are widely used and reported to be efficacious by parents [40], to date only 75 two RCTs have tested their efficacy, yielding mixed results that prevent any recommendation 76 of these exclusion diets as standard treatments [19,8]. Omega-3 fatty acids are increasingly 77 used in ASD despite lack of understanding on which might be the optimal dosage and 78 insufficient evidence of efficacy [18] to endorse all the approaches that they had used with their child in the previous 6 months.…”
mentioning
confidence: 99%